Uelastycznienie form gospodarowania czasem pracy w znowelizowanym kodeksie pracy - Chobot, Andrzej (Wydział Prawa i Administracji UAM, 1996)
The introduction of general flexible working time by the Labour Code left particular solutions to regulations contained in art. 129 of L.C. Since art. 131 of L.C. has been removed, including the part referring to settling individual schedules of working time, it has become all the more imperative to set up directions in collective labour contracts or in working regulations. In view of the lack of directions in collective contracts and working regulations there will appear a severe gap in the law, which would have to be filled by means of interpretation other than linguistic. Collective contracts (and possibly working regulations) ought to guarantee that the workers' individual interests are considered in "taking out" the leisure time for the overtime. Optimally, a worker would decide (or at least co-decide) on the date of "taking out" the leisure time in each case the prolongation did not occur in his interest and on his own initiative (and vice versa - which will probably occur very rarely). The deliberation on the extent of recognizing the labour's interests within the general system of flexible working time, introduced during the work on amending the Code, must emphasize the high merit of time defined by the task scope, with the employee free to prolong or shorten his working time according to his needs, up to stopping work on certain days or even weeks. This is a a truly great merit of the task-effect formula of the employment contract.
Introduction of flexible forms of working time management in the amended labour code